Impact of Covid-19 on the Financial System in Indonesia: Islamic and Conventional Financial System - Firsty Izzata Bella (Ijtihad, 2021)
This research intended to open a discussion regarding the Islamic Financial System (IFS) by providing an in-depth explanation, comparing with the Conventional Financial System (CFS), and seeing the impact of pandemic Covid-19 on the financial system in Indonesia. Through qualitative-descriptive research method specifically utilizing literature studies and case analysis, it is noticeable that Covid-19 has had a very significant impact on the financial system in Indonesia which can be found from money market and capital market. The results depicted that in general, IFS should be applicable not only to Muslim countries, but also to non-Muslim countries. Also, it is known that the impact of the Covid-19 pandemic is real and large, especially on the financial system globally and in Indonesia particularly.